VIETNAMESE-RUSSIAN COOPERATION IN EXPLORATION AND PRODUCTION OF OIL AND GAS FROM 1980 TO THE PRESENT - Thi Huyen Bui (Tạp chí Khoa học Đại học Đà Lạt)
Cooperation in oil and gas exploration and production between Vietnam and Russia has a long history from the 1980s to the present. The cooperation was confirmed and promoted in the first two decades of the 21st century after the two countries established a strategic partnership in 2001 and developed it into a comprehensive strategic partnership in 2012. In this study, we evaluate and analyze the current situation and development trend of the comprehensive strategic partnership between Vietnam and Russia in oil and gas exploration and production. The research shows that the former Soviet Union and the current Russian Federation have supported Vietnam in developing its oil and gas energy industry. Today, both Vietnam and the Russian Federation are very interested in cultivating a cooperative relationship in the oil and gas sector for mutual economic and political interests. The article highlights the economic benefits that Vietnam and the Russian Federation have achieved from this long-term partnership.